2015
DOI: 10.1177/1350650115572198
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurement of roller slip in end-pivoted roller follower valve train

Abstract: Direct-acting tappets and end-pivoted roller followers are the two main types of valve train configurations widely used in passenger car engines. Considerable theoretical and experimental work has been carried out on the direct-acting valve train. However, due to complex nature of the end-pivoted rollers, limited work has been carried out in this area. In roller follower valve train, the roller rotation has a direct impact on the performance in terms of component durability and friction. Roller rotation minimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…During the test, no particular phenomenon of negative slip (percentage slip greater than 2.26) was encountered at all operating conditions as previously reported by the researchers. 68,25 The possible reason for such type of behaviour is the NEDC that follows a pattern of speed over the entire duration. The camshaft speed varies from 375 to 1412 r/min for around 20 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the test, no particular phenomenon of negative slip (percentage slip greater than 2.26) was encountered at all operating conditions as previously reported by the researchers. 68,25 The possible reason for such type of behaviour is the NEDC that follows a pattern of speed over the entire duration. The camshaft speed varies from 375 to 1412 r/min for around 20 min.…”
Section: Resultsmentioning
confidence: 99%
“…6 Relative sliding of mating surfaces operating under marginal lubrication conditions can result in deterioration of the surfaces. 7 Roller slip varies under changing engine revolutions per minute (rpm), lubrication temperature, contact loading along with the lubricant rheology as experimentally investigated by Khurram et al 1,8…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roller slippage has been the subject of a number of theoretical and experimental studies, see for instance Duffy, 2 Khurram et al, 3 Chiu, 4 Ji and Taylor, 5 and Turturro et al 6 As explained by Chiu 4 and also demonstrated in the experiments performed by Bair and Winer, 7 the magnitude of roller slip is strongly governed by the acting contact force, i.e. the higher the contact force the lower the magnitude of experienced roller slippage due to enhanced traction to drive the roller.…”
Section: Introductionmentioning
confidence: 99%